The Relationship Of The Effectiveness On Communication In Learning And Active Participation Of Trainee At The West Sumatra Agricultural Training And Extension Center - Sri Wulan Dari; Setiawati Setiawati (Universitas Negeri Padang, 2022)
This research is motivated by the low activeness of the training participants at the West Sumatra Agricultural Training and Extension Center, this is presumably because it has something to do with the low effectiveness of communication in learning. This study aims to: describe the effectiveness of communication in learning, describe the activeness of the training participants, and see the relationship between the effectiveness of communication in learning and the activeness of the training participants at the West Sumatra Agricultural Training and Extension Center. This type of research is quantitative research with correlational descriptive technique. The study population was all avocado training participants batch 1 and 2 at the West Sumatra Agricultural Training and Extension Center. The data collection technique is in the form of a questionnaire with a data collection tool in the form of a questionnaire. The data analysis technique uses the percentage formula and product moment. The results showed that the effectiveness of communication in learning was categorized as low, the activeness of the training participants was categorized as low, and there was a significant relationship between the effectiveness of communication in learning and the activeness of the training participants at the Training and Agricultural Extension Center of West Sumatra. It is hoped that institutions and instructors will pay attention to the effectiveness of communication in learning because this is related to the learning activities of training participants, and it is suggested to other researchers to be able to look for other variables that affect the learning activities of training participants.Keywords: Activeness, communication effectiveness, training